Response of Syngonium podophyllum L. "White Butterfly" shoot cultures to alternative media additives and gelling agents, and flow cytometric analysis of regenerants - JAIME A. TEIXEIRA DA SILVA (Nusantara Bioscience, 2015)
Abstract. Teixeira da Silva JA. 2015. Response of Syngonium podophyllum L. ‘White Butterfly’ shoot cultures to alternative media additives and gelling agents, and flow cytometric analysis of regenerants. Nusantara Bioscience 7: 26-32. Syngonium podophyllum L. (arrowhead vine) is a popular leafy indoor pot plant whose tissue culture has been established, primarily through in vitro shoot culture, but several interesting aspects have not yet been explored. In this study, cv. ‘White Butterfly’ was used to investigate the response of shoot formation to alternative gelling agents and media additives. Gellan gum (Gelrite®) at 2 g/L resulted in greater leaf production, plantlet fresh weight and higher chlorophyll content (SPAD value) than all other gelling agents tested, including agar, Bacto agar, phytagel, oatmeal agar, potato dextrose agar, barley starch and corn starch, when on a basal Hyponex® (NPK = 6.5: 6: 19; 3 g/L) medium. Several alternative liquid medium additives tested (low and full-fat milk, Coca-Cola®, coffee, Japanese green, Oolong, and Darjeeling teas) negatively impacted plant growth, stunted roots and decreased chlorophyll content (SPAD value) of leaves. Plant growth on medium with refined sucrose or table sugar responded similarly. Poor growth was observed when crude extract from a high rebaudioside-containing stevia (Stevia rebaudiana Bertoni) line - an artificial sweetener - was used. Leaf tissue from the control did not show any endopolyploidy but low levels of endopolyploidy (8C) were detected in some treatments.